Representations of Privileged Motherhood in Nineteenth-Century Literature: A Comparative Analysis of Leo Tolstoy’s Anna Karenina and Kate Chopin’s The Awakening - Alhassani, Dina (AUC Knowledge Fountain, 2013)
The heroines of Tolstoy’s Anna Karenina and Chopin’s The Awakening enjoy the autonomy of privileged motherhood in the nineteenth century. This role allows them the opportunities to forge their identities independent of most of the societal expectations which defined nineteenth-century feminine gender roles. The spinster enjoyed independence and yet had limited social interactions due to her perceived lack of femininity. By contrast, most mothers from lower and middle class backgrounds had fulfilled the idealized maternal role at the expense of independence and self-determination. In the context of nineteenth-century gender roles, the privileged mother enjoys the combined best aspects of spinsterhood (independence) and motherhood (perceived biological essentialism and social acceptance). The similarities between the positions of the protagonists of Anna Karenina and The Awakening are striking when one considers that these novels were written in dissimilar cultures and geographical locations. Russian nobility was based on family connections and historical precedence dating back centuries, whereas Louisiana nobility was relatively recent and implied wealth. The depictions of privileged motherhood in both books are different, but both represent a cross-cultural paradigm shift in the roles of women that would reflect the concerns of first wave feminists including Elizabeth Cady Stanton who wrote: “the woman is uniformly sacrificed to the wife and mother” (14). The novels depict women who are wives and mothers and yet retain their agency due to their status. Their journeys represent a rebellion against these gender roles. Their privileged mother statuses do not grant them complete autonomy and the tensions between their relative autonomy and an ideal autonomy lead to suicide scenes that represent a pursuit of an ultimately sublime experience